The Importance of Curriculum Management in ECE Institutions - Edi Waluyo; Eko Supraptono; Agus Hermanto; Fakhruddin Fakhruddin (Universitas Negeri Semarang, 2021)
This research aimed to describe curriculum management in ECE institutions systematically. A survey research design was used in this research. The research samples were principals and teachers from the state, private, and religious-based ECE institutions in Semarang. The data collection technique was carried out through questionnaires, observations, and interviews. Based on the findings, curriculum management in ECE institutions gives good contributions to the development of curriculum documents, annual programs, semester programs, weekly programs, and daily programs. Curriculum management creates effective work steps in designing, organizing, implementing, and evaluating a curriculum.